2020
DOI: 10.1021/acsenergylett.0c01385
|View full text |Cite
|
Sign up to set email alerts
|

In SituPhase Transformation on Nickel-Based Selenides for Enhanced Hydrogen Evolution Reaction in Alkaline Medium

Abstract: Identification of the active species in electrocatalysts toward hydrogen evolution reaction (HER) is of great significance for the development of the catalytic industry; however, it is still the subject of considerable controversy. Herein, we applied operando synchrotron X-ray powder diffraction (SXRD) in the NiSe 2 electrocatalyst system, and an in situ phase transformation from cubic NiSe 2 to hexagonal NiSe was revealed. The NiSe phase showed an enhanced catalytic activity. Operando Raman spectroscopy verif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
123
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(124 citation statements)
references
References 43 publications
1
123
0
Order By: Relevance
“…It can be observed that, for (Ni, Fe)Se 2 /CC sample, the characteristic Raman peaks located at 132, 145, 206, and 232 cm −1 are assigned to (Ni, Fe)Se 2 . [ 35 ] But for the sample after electrodeposition, three other broaden peaks located at ≈484, 552, and 678 cm −1 appear, which are corresponding to the characteristic Raman peaks of amorphous NiFe(OH) x . [ 36 ] The XRD and Raman results show that the amorphous‐crystalline NiFe(OH) x /(Ni, Fe)Se 2 heterostructure has been successfully fabricated.…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed that, for (Ni, Fe)Se 2 /CC sample, the characteristic Raman peaks located at 132, 145, 206, and 232 cm −1 are assigned to (Ni, Fe)Se 2 . [ 35 ] But for the sample after electrodeposition, three other broaden peaks located at ≈484, 552, and 678 cm −1 appear, which are corresponding to the characteristic Raman peaks of amorphous NiFe(OH) x . [ 36 ] The XRD and Raman results show that the amorphous‐crystalline NiFe(OH) x /(Ni, Fe)Se 2 heterostructure has been successfully fabricated.…”
Section: Resultsmentioning
confidence: 99%
“…During the past several years, the earth‐abundant transition metal chalcogenides (especially selenides such as NiSe, NiSe 2 , CoSe 2 ) have demonstrated their attractive efficacy for water splitting (HER and OER) as noble metal‐free electrocatalysts. [ 9–13 ] They have also been applied for the unique organic upgrading reactions due to their high electrocatalytic activity, good metallic property for promoting the electron conduction, and high selectivity for generating value‐added products. [ 14,15 ] In addition to controlling the chemical compositions of electrocatalysts, the electrocatalytic performance could be further improved by nanostructure engineering with optimized geometric features.…”
Section: Introductionmentioning
confidence: 99%
“…32 They show that in the initial reaction stage of HER, the outermost layer of selenides (NiSe 2 ) will ionize in strong KOH solution, the Se 2 2will leach out and combine with the dissolved oxygen to generate SeO x , and accompanied by the generation of Ni(OH) 2 /NiOOH. 52 The specific mechanism is shown as follows: 32 (1)…”
Section: The Role Of Seo X Film Thicknessmentioning
confidence: 99%